Investigation of catalyst‐transfer condensation polymerization for synthesis of poly(p‐phenylenevinylene). Issue 18 (27th June 2014) - Nojima, Masataka; Ohta, Yoshihiro; Yokozawa, Tsutomu
ABSTRACT Kumada‐Tamao coupling polymerization of 1, 4‐dialkoxy‐2‐bromo‐5‐(2‐chloromagnesiovinyl)benzene (1) and 1, 4‐dialkoxy‐2‐(2‐bromovinyl)‐5‐chloromagnesiobenzene (2) with a Ni catalyst and Suzuki‐Miyaura coupling polymerization of 2‐2‐[(2, 5‐dialkoxy‐4‐iodophenyl)]vinyl‐4, 4, 5, 5‐tetramethyl‐1, 3, 2‐dioxaborolane (3), its bromo counterpart 4, and 2, 5‐dialkoxy‐4‐(2‐bromovinyl)phenylboronic acid (5) with a Pd initiator were investigated under catalyst‐transfer condensation polymerization conditions for the synthesis of well‐defined poly(p‐phenylenevinylene) (PPV). The Kumada‐Tamao polymerization of vinyl Grignard‐type monomer 1 with Ni(dppp)Cl2 at room temperature did not proceed, whereas aryl Grignard‐type monomer 2 afforded oligomers of low molecular weight. Matrix‐assisted laser desorption ionization time‐of‐flight (MALDI‐TOF) mass spectra of the polymer obtained from 2 implied that the Grignard end group reacted with tetrahydrofuran to terminate polymerization. On the other hand, Suzuki‐Miyaura polymerization of vinyl boronic acid ester type monomers 3 and 4 and phenylboronic acid type monomer 5 with a Pd initiator and aqueous KOH at −20 °C to room temperature yielded the corresponding PPV with high molecular weight within a few minutes. However, the molecular weight distribution was broad, and MALDI‐TOF mass spectra showed the peaks of polymers bearing no initiator unit at the chain end, as well as those of polymers with the initiator unit. These results indicated that intermolecular chain transfer of the Pd catalyst occurred. Dehalogenation and disproportionation of the growing end also took place as side reactions. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 2643‐2653